Perceived Motivators and Constraints among Regular Players of Pick-Up Basketball Games: 經常參加籃球運動群體的動機與障礙 - WANG, Jianyu; LIU, Wenhao; BIAN, Wei; TAN, Jiangong (Asian Journal of Physical Education & Recreation, 2010)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of this study was to examine perceived motivators and constraints among regular players of pick-up basketball games. Sixty-five basketball players were invited to participate in the study. The instrument assessing participants’ perceived motivators and constraints of participating in pick-up basketball games was adapted from the works on leisure motivators and constraints. Results indicated that the primary motivators for the players playing pick-up basketball games were having fun (77.9%), improving physical fitness (55.9%), becoming fit (52.9%), and improving basketball skills (41.2%). The major constraints the players perceived were lack of leisure time (55.9%), lack of basketball courts (45.6%), hard to find friends to play with (17.6%), and too much work (16.2%). The findings of the study may imply that in order to promote physical activity policy-makers should help create better physical environments such as the access to the basketball courts. Additionally, physical education professionals must help young people develop motor skills to enjoy the activity. 本文旨在揭示經常參加籃球運動群體的動機與障礙。六十五位經常參加籃球運動的人士應邀參加本研究。結果顯示經常參加籃球運動主要的動機包括有興趣(77。9%) 、提高體能(55。9%) 、改進健康 (52。1%) 、提高籃球技術 (41。2%) 。主要障礙包括缺少休閒時間(55。9%) 、缺乏場地 (45。6%) ，難以找到朋友一起參與 (17。6%) 、太多工作 (16。2%) 。本研究結果表明為了更好促進大眾體育鍛煉﹐決策者須考慮改善體育鍛煉的環境，同時體育專業人士應幫助青少年發展運動技能。